Life Cycle Assessment based identification of Environmental Hotspots in Commercial Trawl Fisheries of Kerala and Mitigation Strategies - Ravi, Renju; Dhiju Das, P. H.; Edwin, Leela (Fishery Technology, 2020)
Life Cycle Assessment (LCA) is used to identify environmentally preferred products or processes and can be used as a support tool for decisionmaking and policy development. In India, LCA of trawl fishing, wherein impact categories such as Global warming potential (GWP), Abiotic depletion potential (fossil) (ADP), Acidification potential (AP), Eutrophication potential (EP), Marine aquatic ecotoxicity potential (MAETP), Ozone layer depletion potential (ODP) and Photochemical ozone creation potential (POCP), are not studied. In this study, LCA and carbon footprint of fish production by trawlers operating in Kerala fisheries sector has been carried out. Direct energy input for fishing operations due to consumption of fuel account for 75 to 90% of the total energy inputs when compared with energy inputs associated with vessel construction and maintenance, fishing gear and others. The study showed that, the impact categories such as GWP, ADP, AP, EP and POCP are predominantly related to the consumption of diesel for vessel operation and hence identified as the main hotspot with respect to environmental burdens which need focussed action in mitigation approaches. The results of this study delineates approaches for reducing carbon footprint of the trawl caught resources in Kerala.